The Influence of Good Corporate Governance Mechanisms on Financial Performance Mediated by Financial Risk - Yovita Putri Aprilia; Nur Anisah (Proceeding International Conference on Digital Education and Social Science, 2025)
This research examines the impact of Good Corporate Governance (GCG) mechanisms on financial performance, with financial risk acting as a mediating variable, in banking firms listed on the Indonesia Stock Exchange (IDX) for the 2022–2024 period. The study is motivated by the crucial role of effective corporate governance in ensuring sustainable banking performance amid dynamic global economic developments. A quantitative approach with a causal research design was employed. The sample consisted of banking companies selected using purposive sampling, based on the availability of complete financial reports and consistent disclosure of GCG practices. Secondary data were collected from published annual reports and financial statements. The data were analyzed using multiple linear regression and path analysis to assess both direct and indirect relationships among the variables. The findings demonstrate that GCG mechanisms exert a positive and significant influence on financial performance. In addition, financial risk has a negative effect on financial performance and serves as a partial mediator in the relationship between GCG and financial performance. These results suggest that the effective implementation of GCG not only enhances financial performance directly but also indirectly through improved financial risk management. This study is expected to provide valuable insights for company management, investors, and regulators in reinforcing corporate governance practices and maintaining stability within the banking industry.